Unlocking the power of precision medicine for pediatric low-grade gliomas: molecular characterization for targeted therapies with enhanced safety and efficacy - Cipri, Selene; Del Baldo, Giada; Fabozzi, Francesco; Boccuto, Luigi; Carai, Andrea; Mastronuzzi, Angela (Frontiers in Oncology, 2023)
In the past decade significant advancements have been made in the discovery of targetable lesions in pediatric low-grade gliomas (pLGGs). These tumors are the most prevalent brain tumors in children, accounting for 30-50% of brain tumors in childhood. While pLGGs generally have a favorable prognosis, a minority can exhibit aggressive behavior. The latest 2021 WHO classification of pLGGs places a strong emphasis on molecular characterization for significant implications on prognosis, diagnosis, management, and the development of personalized treatment. With the help of technological advances and new applications in molecular diagnostics, the molecular characterization of pLGGs has revealed that tumors that appear similar under a microscope can have different genetic and molecular characteristics. Therefore, the new classification system divides pLGGs into several distinct subtypes based on these characteristics, enabling a more accurate strategy for diagnosis and personalized therapy based on the specific genetic and molecular abnormalities present in each tumor. This approach holds great promise for improving outcomes for patients with pLGGs, highlighting the importance of the recent breakthroughs in the discovery of targetable lesions.